Applied high-intensity interval cardio yoga improves cardiometabolic fitness, energetic contributions, and metabolic flexibility in healthy adults - Park, So-Young; Yang, Woo-Hwi (Frontiers in Physiology, 2023)
Purpose: Currently, there is no interventional approach to increase the intensity of Surya Namaskar a popular hatha yoga sequence used worldwide. Therefore, this study investigated how tempo-based high-intensity interval cardio yoga (HIICY) and traditional interval hatha yoga (TIHY) affects cardiometabolic fitness in active adults. Methods: Twenty physically active male and female individuals were randomly separated into HIICY (5 males, 5 females, 1.5 s tempo) and TIHY (5 males, 5 females, 3 s tempo) groups. The intervention included twelve exercise sessions for 4 weeks in both groups. Participants conducted a ramp test to determine their maximal oxygen uptake (V˙O2max), maximal velocity at V˙O2max (vV˙O2max), and maximal heart rate (HRmax). Afterward, they performed a 10-min high-intensity cardio yoga test (HICYT) to determine heart rate (HRpeak and HRmean), oxygen uptake (V˙O2peak and V˙O2mean), respiratory exchange ratio (RER), blood lactate concentrations (La−peak and ∆La−), fat and carbohydrate oxidations (FATox, CHOox), and energetic contributions (oxidative; WOxi, glycolytic; WGly, and phosphagen; WPCr, total energy demand; WTotal). Results:V˙O2max and vV˙O2max showed time and group × time interactions (p < 0.01, p < 0.0001, p < 0.001, respectively). V˙O2max after HIICY was significantly higher than in pre-testing and following TIHY (p < 0.001, p < 0.0001, respectively). V˙O2peak, V˙O2mean, RER, HRpeak, and HRmean during the 10-min HICYT showed significant time effects (p < 0.05). ∆La− indicated a group × time interaction (p < 0.05). Group x time interaction effects for FATox at the fourth and sixth minute were observed (p < 0.05, respectively). Absolute (kJ) and relative (%) WOxi, WGly, and WTotal showed time and group × time interaction effects (p < 0.05, p < 0.01, respectively). Furthermore, %WGly was reduced following HIICY (p < 0.05). Additionally, V˙O2max and vV˙O2max were highly correlated with WOxi in kJ (r = 0.91, 0.80, respectively). Moderate to high correlations were observed among CHOox, FATox, and absolute V˙O2max (r = 0.76, 0.62, respectively). Conclusion: A 4-week period of HIICY improved cardiometabolic fitness, oxidative capacity, and metabolic flexibility compared with TIHY, in physically active adults. Therefore, HIICY is suitable as HY-specific HIIT and time-efficient approach for relatively healthy individuals.